2017
DOI: 10.22547/ber/9.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Synchronicity and Information Environment

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The average value of the firm's market model explains the 13% variation in the firm's PSX stock returns. This low average R squared indicates that the predictability power of the market model is low and that it is possible that the companyspecific variables can contribute more (or increase) in idiosyncratic returns (Fraz and Hassan, 2017).…”
Section: Descriptive Statisticmentioning
confidence: 99%
“…The average value of the firm's market model explains the 13% variation in the firm's PSX stock returns. This low average R squared indicates that the predictability power of the market model is low and that it is possible that the companyspecific variables can contribute more (or increase) in idiosyncratic returns (Fraz and Hassan, 2017).…”
Section: Descriptive Statisticmentioning
confidence: 99%
“…The study revealed that there is a link between the price of a share and a firm's size. Fraz and Hassan (2017) in their study concluded that pricing fluctuations in large corporations have an impact on market synchronicity. Asif et al (2016) found that stock prices have a substantial correlation with the macro-economic variables.…”
Section: Financial Information and Share Price Movements In Secondary...mentioning
confidence: 99%
“…Multifactor model using R 2 , the proxy of SPS is used as EMI and it is measured by using the capital asset pricing model. To estimate, EMI with other trading partners the degree of association is calculated by using the return of stock index of trading partner and MSCI global index with the return of Pakistan's stock index (An & Zhang, 2013;Vithessonthi & Kumarasinghe, 2016;Fraz & Hassan, 2017;Farooq, Ahmed, & Bouaddi, 2018).The study uses monthly market returns of Pakistan's equity market and MSCI global index with the returns of trading partners' equity market for36 months to estimate R 2 for each year from 1998 to 2016. The following model is used to estimate R 2 .…”
Section: Dependent Variablementioning
confidence: 99%